The Press, Politics and Democratic Stability - Oni, Kayode Julius (African Journal of Stability and Development (AJSD), 2018)
It’s axiomatic to note that, there is indeed an inextricable or close nexus between the realm of mass communication and that of politics. This to a large extent derives from the goal the two seek to achieve. Communication is the oil that lubricates the engine of political and social relations. Politics is meant to realise the goal of the society or to promote the common good. The myriads of political activities in the state and around its agencies can have great impact on the society at large through the instrumentality of mass communication. Arguably, while the complex operational environments of the mass media in older democracies are relatively vibrant and congenial, the same cannot be said of the new democracies. Yet as agents that are meant to check executive recklessness on the one hand and as instruments of sensitisation and mobilisation, the press in the advanced democracies have their own limitations that can hardly be ignored. The peculiar domain in which mass media operate in the less developed societies raises many germane issues that demands answers. The paper seeks to interrogate the nature and character of politics visible in African states that engendered hostile environment for the press. The study contends that there is the dire need for a paradigm shift from sensational reporting to messages that are capable of tilting the mass of the people towards the realisation of the goal of the society, including democratic stability